2008
DOI: 10.1111/j.1939-1676.2007.0008.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival Characteristics and Prognostic Variables of Dogs with Mitral Regurgitation Attributable to Myxomatous Valve Disease

Abstract: Background: There are few studies evaluating the natural history and prognostic variables in chronic mitral valve disease (CMVI) in a heterogeneous population of dogs.Objectives: To estimate survival and prognostic value of clinical and echocardiographic variables in dogs with CMVI of varying severity. Five hundred and fifty-eight dogs belonging to 36 breeds were studied.Methods: Dogs were included after clinical examination and echocardiography. Long-term outcome was assessed by telephone interview with the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
369
8
17

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(451 citation statements)
references
References 37 publications
36
369
8
17
Order By: Relevance
“…Given that a previous study has shown that the parasympathetic tone decreases with echocardiographic indices of MMVD,15 the HRV findings in this study might suggest that dogs with syncope have a more advanced stage of MMVD than do dogs without. This is also suggested in a study of survival characteristic in dogs with MMVD, showing that syncope, LA/Ao>1.7, and E‐wave transmitral peak velocity (Emax) >1.2 m/s were significantly associated with increased risk of death 11. However, this is in conflict with the echocardiographic findings in our study where little difference in echocardiographic variables was observed between dogs with and without a history of syncope (Table 1).…”
Section: Discussionsupporting
confidence: 49%
“…Given that a previous study has shown that the parasympathetic tone decreases with echocardiographic indices of MMVD,15 the HRV findings in this study might suggest that dogs with syncope have a more advanced stage of MMVD than do dogs without. This is also suggested in a study of survival characteristic in dogs with MMVD, showing that syncope, LA/Ao>1.7, and E‐wave transmitral peak velocity (Emax) >1.2 m/s were significantly associated with increased risk of death 11. However, this is in conflict with the echocardiographic findings in our study where little difference in echocardiographic variables was observed between dogs with and without a history of syncope (Table 1).…”
Section: Discussionsupporting
confidence: 49%
“…Degenerative mitral valve disease (DMVD) characterized by myocardial dysfunction with eccentric cardiac remodeling is the leading cause of heart failure in small breed dogs 1, 2. Myocardial systolic or diastolic dysfunction accrues from histopathologic changes that cause myocardial decompensation, which in turn induces clinical signs such as cough, dyspnea, and exercise intolerance 3, 4, 8, 9, 10.…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of congestive heart failure in small breed dogs is degenerative mitral valve disease (DMVD) characterized by poor coaptation of mitral valve cusps, leading to mitral regurgitation 1, 2. In chronic heart diseases, accurate evaluation of myocardial function is important, because it aids clinicians in planning medical treatment and formulating a prognosis 3, 4.…”
mentioning
confidence: 99%
“…Systolic function has been suggested to decrease in dogs with naturally acquired MMVD2, 3 and in dogs with experimentally induced MR 20, 21. However, identification of systolic dysfunction is challenging in dogs with MMVD22; EF, FS, and PEP/ET at rest and dobutamine infusion could not detect systolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%